The Three-Component Feedback System of Nurses' Power, Empowerment, and Job Performance - Wafa'a F. Ta'an; Mohammed M. Al-Hammouri; Jehad A. Rababah (Jordan University of Science and Technology, 2022)
Quality service provision depends on the performance of the service providers; therefore, enhancing an empowering work environment is crucial to achieving excellence. This study examined the intercorrelation between structural empowerment, nurses perceived formal and informal power, and their job performance. Nurses perceived only a moderate level of power in their work environment with the highest performance quality in the area of critical care. The model “the three-component feedback system of power, empowerment, and job performance” was tested using the structural equation model. The data from 200 nurses strongly fit with the proposed model. This study proposed that job performance, power, and empowerment are involved in a loop of feedback system in which each variable in the loop affects other variables either directly or through other variables in the loop. Applying staff improvement plans can begin in one component of the system, and the progress will eventually enhance the other components. Keywords: Nursing management, power, empowerment, job performance.